The Effect of Discounts and Free Shipping on Purchase Decisions on the Shopee Marketplace (Case Study of Management Study Program Students, Class of 2022, University of Labuhanbatu) - Ayu Rahmawati; Aulia Indra; Bayu Eko Broto (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study examines the influence of discounts and free shipping on purchasing decisions on the shopee marketplace among management students from the 2022 intake at Labuhanbatu University. This quantitative study used a Google Forms questionnaire and simple random sampling to collect 71 respondents. Multiple linear regression was used in SPSS 25. All research indicators were valid and reliable, according to SPSS test results. The t-test showed that discounts and free shipping had a positive and significant effect on purchasing decisions on the shopee marketplace. In the F-test, all variables simultaneously had a positive and significant effect on purchasing decisions on the shopee marketplace.